2019
DOI: 10.1101/743674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA levels in ventral visual cortex decline with age and are associated with neural distinctiveness

Abstract: Age-related neural dedifferentiationreduced distinctiveness of neural representations in the aging brain-has been associated with age-related declines in cognitive abilities. But why does neural distinctiveness decline with age? Based on prior work in non-human primates, we hypothesized that the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) declines with age and is associated with neural dedifferentiation. To test this hypothesis, we used magnetic resonance spectroscopy (MRS) to measure GABA and f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…For example, using MR spectroscopy to quantify GABA concentrations in occipital voxels, Simmonite et al (2019) found that lower occipital GABA levels in older adults were associated with declines in fluid processing abilities. Furthermore, Chamberlain et al (2019;preprint) reported that individual differences in the category specificity of face versus house representations were linked to individual differences in VVC GABA concentrations in older adults, indicating a role of GABA in age-related neural dedifferentiation (see also Cassady et al, 2019;Gagnon et al, 2019;Lalwani et al, 2019). These findings substantiate the key role of proficient (particularly GABAergic) neuromodulation for high-fidelity (i.e., stable and distinct) neural representations and cognitive performance and lay the ground for future studies aiming to understand how agerelated deficits in neuromodulation are related to neural dedifferentiation across representational levels.…”
Section: Neural Dedifferentiation As a Consequence Of Age-related Neumentioning
confidence: 99%
“…For example, using MR spectroscopy to quantify GABA concentrations in occipital voxels, Simmonite et al (2019) found that lower occipital GABA levels in older adults were associated with declines in fluid processing abilities. Furthermore, Chamberlain et al (2019;preprint) reported that individual differences in the category specificity of face versus house representations were linked to individual differences in VVC GABA concentrations in older adults, indicating a role of GABA in age-related neural dedifferentiation (see also Cassady et al, 2019;Gagnon et al, 2019;Lalwani et al, 2019). These findings substantiate the key role of proficient (particularly GABAergic) neuromodulation for high-fidelity (i.e., stable and distinct) neural representations and cognitive performance and lay the ground for future studies aiming to understand how agerelated deficits in neuromodulation are related to neural dedifferentiation across representational levels.…”
Section: Neural Dedifferentiation As a Consequence Of Age-related Neumentioning
confidence: 99%
“…In the anatomical control region (occipital cortex), there was a qualitatively similar pattern of age-related inhibitory decline, consistent with previous reports 28,29 . However this was not statistically significant, likely reflecting the impact of quality controls that reduced the size of the occipital dataset and consequently reduced power (Table S1 S5.…”
Section: -Minutes 24-hourssupporting
confidence: 90%
“…Across cortex, E:I is disrupted because γ-aminobutyric acid (GABA), the major inhibitory neurotransmitter, declines with age, both in animals 16,17 and humans 15,[18][19][20][21][22][23][24][25][26] . Regional decline of cortical GABA causes a loss of inhibitory tone, and this is associated with decrements in functions localized to the affected regions [27][28][29] . For example, in somatosensory cortex lower GABA (i.e., higher E:I) is associated with poorer tactile discrimination, both in young and old adults 20,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies also demonstrated a relationship between a decline of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and neural distinctiveness. Combining magnetic resonance spectroscopy (MRS) to measure GABA with functional MRI, Chamberlain et al (2019) found that older adults had lower GABA levels (see also Simmonite et al, 2019) and less distinct activation patterns in the ventral visual cortex. Furthermore, individual differences in GABA predicted individual differences in distinctiveness (see for similar results with regard to the discrimination of auditory stimuli and GABA levels in the auditory cortex (see Lalwani et al, 2019, for similar results with regard to the discrimination of auditory stimuli and GABA levels in the auditory cortex).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced inhibition by GABAergic interneurons might impair the resolution of conflict between neural representations and result in less distinct representations (Chamberlain et al, 2019;Lalwani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%